2000
DOI: 10.1161/01.hyp.35.1.418
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Renal Medullary Nitric Oxide Synthase Activity Protects From Norepinephrine-Induced Hypertension

Abstract: Abstract-Studies were performed in conscious Sprague-Dawley rats to determine the role of the ␣ 2 -adrenergic receptor-mediated increase in the renal medullary nitric oxide synthase (NOS) activity as a counterregulatory mechanism of blood pressure control in response to increased renal adrenergic stimulation. A subpressor dose of norepinephrine (NE, 8 g ⅐ kg Ϫ1 ⅐ h Ϫ1 ) was infused intravenously, and NOS activity was determined with arginine-citrulline conversion by high-performance liquid chromatography in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…7, in rats that received the subpressor chronic medullary infusion of L-NAME, AVP led to a sustained elevation of blood pressure (117). Similar studies were carried out to determine the responses to chronic intravenous infusions of subpressor doses of ANG II (116) and NE (118). Also shown in Fig.…”
Section: Renal Medullary No Protects Against Chronic Ang Ii- Ne- Anmentioning
confidence: 89%
See 2 more Smart Citations
“…7, in rats that received the subpressor chronic medullary infusion of L-NAME, AVP led to a sustained elevation of blood pressure (117). Similar studies were carried out to determine the responses to chronic intravenous infusions of subpressor doses of ANG II (116) and NE (118). Also shown in Fig.…”
Section: Renal Medullary No Protects Against Chronic Ang Ii- Ne- Anmentioning
confidence: 89%
“…A dose of L-NAME (75 g ⅐ kg Ϫ1 ⅐ h Ϫ1 ) was used that did not reduce basal MBF Ͼ5% when administered into the medullary interstitial space chronically for 2 wk (118). The same dose of L-NAME that significantly attenuated acute increases of medullary [NO] produced by intravenous infusions of subpressor amounts of ANG II, NE, and AVP (116)(117)(118). Doses of ANG II (3.0 ng ⅐ kg Ϫ1 ⅐ min Ϫ1 ), NE (0.1 g ⅐ kg Ϫ1 ⅐ min Ϫ1 ), and AVP (2.0 ng ⅐ kg Ϫ1 ⅐ min Ϫ1 ) were determined that when administered intravenously did not result in elevations of mean arterial pressure Ͼ5 mmHg when infused for 5-7 days to normal Sprague-Dawley rats (see Fig.…”
Section: Renal Medullary No Protects Against Chronic Ang Ii- Ne- Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, it is known that both angiotensin and increased renal nerve activity stimulate vasodilating prostaglandins (PGI 2 and PGE 2 ) in the kidney (4). Previous studies have shown an upregulation of NO synthase activity with ␣-adrenergic activity (15,17). In concert with these previous results, in the present study, plasma NO levels during endotoxemia were lower in mice with renal denervation.…”
Section: Discussionmentioning
confidence: 99%
“…ANG II, norepinephrine, and vasopressin stimulate release of NO in the medulla (121,150,151,181,185). Subpressor infusion of N G -nitro-Larginine methyl ester into the renal interstitium does not affect medullary blood flow or PO 2 but enables otherwise ineffective doses of ANG II (185) norepinephrine (151,181), or vasopressin (150) to induce a fall in these parameters. Taken together, the data support the conclusion that medullary NO production has a tonic effect in maintaining perfusion and protecting the medulla from ischemic injury.…”
Section: Medullary Po2 and Perfusion Of The Medullamentioning
confidence: 99%